Hedge and safe-haven properties of Cryptocurrencies: evidence in east asia-5 market - Chiang-Ching Tan; Pick Soon Ling; Siew-Ling Sim; Kelvin Lee Yong Ming (Cogent Economics & Finance, 2023)
This study examined the capabilities of six cryptocurrencies as a hedge and safe haven against the stock indices and foreign exchange rate in the East Asia-5 markets. According, MGARCH-DCC was adopted and implemented in data collection processes together with Rathner and Chiu regression method, which spanned from April 2013 to December 2019. The results revealed that these cryptocurrencies had dissimilar hedging and safe haven capabilities across various stock indices and exchange rates in the East Asia-5 markets. In particular, Bitcoin, Litecoin, and Ethereum offered strong hedge properties on most of the East Asia-5 equity indices. Moreover, Bitcoin and Litecoin only provided a safe haven for Japanese Yen currency, while Taiwanese equity indices and Chinese Yuan currency can be safely protected via an investment into Stellar.
Keywords: 330; Bitcoin; cryptocurrencies; East Asia-5 markets; MGARCH-DCC; safe-haven; stock indices